Green Branding to Create Green Competitive Advantage in McDonalds Indonesia Fast Food Company - Fatimah, Fatimah; Efriyanto, Efriyanto; Lia Ekowati; Redyanita, Hastuti (International Review of Management and Marketing, 2025)
The practice of greenwashing is a problem for companies that are committed to building green branding honestly and earnestly as a green competitive advantage, including McDonalds Indonesia’s business. This fast food company has implemented a green business strategy but has not fully implemented green branding. It is necessary to study green satisfaction, green brand image, green trust and green awareness as important parts that shape the perception of green branding. The purpose of this study is to analyze the influence of green branding consisting of green satisfaction, green brand image, green trust and green awareness on green competitive advantage with greenwashing as a moderation variable. The sampling method uses purposive sampling and to determine the sample size is used by Lemeshow formulation with a total of 481 throughout Indonesia. Data analysis using SmartPLS 4. The findings of this study have a positive and significant influence between green branding consisting of green satisfaction, green brand image, green trust and green awareness on Green Competitive Adventive, simultaneously green satisfaction, green brand image, green trust and green awareness have a positive effect on green competitive advantage and greenwashing does not strengthen the influence of green satisfaction, green brand image, green trust and green awareness of green competitive advantage.